A Method Trial for Determining the Burial Season of Graves Using Drone Images: The Example of the Malazgirt Project - Dölek, İskender (Ali ULVİ, 2023)
In 2020, a project called “Detection, Historical and Archaeological Survey Project of the Battlefield of Malazgirt” was initiated with the support of the Ministry of Culture. Within the scope of the project, excavations were carried out in different areas within the borders of Malazgirt district in order to detect traces of the Battle of Malazgirt, and many finds (objects and bones) thought to belong to the war were reached. Aging on objects and bones will give an approximate date. The fact that the battle took place on August 26, 1071 also necessitates a seasonal assessment of the human bones thought to belong to the war. In this study, a method has been tried to be developed to determine the burial season. For this purpose, the spatial equivalents of some elements of burial traditions (such as the direction of the tombs, the direction of the qibla) were combined with digital images produced by Unmanned Aerial Vehicles (UAV), which can be integrated with Geographic Information Systems (GIS). It is thought that the proposed model can be used to determine the seasons of burials, including burials belonging to certain periods and cultures, for excavations in our country. © Author(s) 2023.
Dron Görüntüleri Kullanılarak Mezarların Gömü Mevsiminin Belirlenmesine Yönelik Bir Yöntem Denemesi: Malazgirt Projesi Örneği
Keywords: Archeology; Drone; Gis; Orthophoto; Photogrammetry